Linguistic genocide in education or Worldwide diversity and human rights? - Skutnabb-Kangas, Tove (Hyderabad, 2008)
In this powerful multidisciplinary new book, Tove Skutnabb-Kangas shows how most indigenous and minority education contributes to linguistic genocide according to United Nations definitions. Her starting point is that it is normal and desirable for people, groups, countries, and schools to be multilingual and multicultural. She brings together theoretical concerns and research areas which no other contemporary book synthesizes: linguistic human rights; minority and multilingual education; language ecology and threatened languages; the relationship between biodiversity and linguistic and cultural diversity; the impact of linguistic imperialism and unequal power relations on ethnicity, linguistic, and cultural competence, and identities. Theory is combined with a wealth of factual encyclopedic information and with many examples and vignettes. The examples come from all parts of the world and try to avoid Eurocentrism. Oriented toward theory and practice, facts and evaluations, reflection and action, the book prompts readers to find information about the world and their local contexts, to reflect, and to act. It is essential reading for scholars, students, and practitioners in the fields of language and society, language policy and language planning, the sociology of education, critical pedagogy, comparative education, educational linguistics, minority studies, cultural studies, human rights, ethnolinguistics, anthropology, and ecological issues. Reviews: "This work, by one of the leading scholars of linguistic human rights, presents a provocative, engaging, grand synthesis. It makes a major contribution by bringing together a number of contemporary theoretical and research orientations as evidenced by its focus on linguistic human rights, linguistic ecology, and the impact of linguistic imperialism. In addition, it provides basic insights on anti-racist education.
Keywords: Social conflict